Robust monitoring of the Eurasian lynx Lynx lynx in the Slovak Carpathians reveals lower numbers than officially reported. Issue 3 (7th August 2017) - Kubala, Jakub; Smolko, Peter; Zimmermann, Fridolin; Rigg, Robin; Tám, Branislav; Iľko, Tomáš; Foresti, Danilo; Breitenmoser-Würsten, Christine; Kropil, Rudolf; Breitenmoser, Urs
Abstract: The Eurasian lynx Lynx lynx population in the Carpathian Mountains is considered to be one of the best preserved and largest in Europe and hence is a source for past and current reintroduction projects in central Europe. However, its status in Slovakia has been reported to the European Commission on the basis of hunters´ reports and expert estimates that have never been validated by a robust scientific approach. We conducted the first camera-trapping surveys to estimate the density of Eurasian lynx in Slovakia by means of spatial capture–recapture models in two reference areas during 2011–2015. We estimated population density per 100 km 2 of suitable lynx habitat (posterior SD) as 0.58 ± SD 0.13 independent individuals (adults and subadults) in the Štiavnica Mountains and 0.81 ± SD 0.29 in Veľká Fatra National Park and surroundings. These are the lowest densities estimated using spatial capture–recapture models so far reported for the species, suggesting the lynx population in Slovakia is below carrying capacity. We suspect that low densities may be attributable to undetected human-caused mortality. Our results imply that official game statistics are substantially overestimated. Moreover, the lynx population in Slovakia may not be at favourable conservation status as required by the EU Habitats Directive. We therefore call for a thorough assessment of the density and trend of the Slovak Carpathian lynx population, and the establishment of a scientifically robust monitoring system.